2019
DOI: 10.1007/s42995-019-00003-4
|View full text |Cite
|
Sign up to set email alerts
|

Vertical variation in Vibrio community composition in Sansha Yongle Blue Hole and its ability to degrade macromolecules

Abstract: With the advantages of wide distribution, fast growth, and broad metabolic spectrum to organic carbon compounds, Vibrio may play an important role in organic carbon cycling. However, the ecological roles of Vibrio in many marine environments have not been explored. Here, the world's deepest 'blue hole', the Sansha Yongle Blue Hole (SYBH) in the South China Sea, which is a geographically semi-enclosed environment featuring unique chemical characters, was investigated. The abundance, diversity and carbon source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 68 publications
3
21
1
1
Order By: Relevance
“…4, 6). A recent survey focused on the distribution of the bacterial genus Vibrio in the SYBH also showed a clear vertical stratification of the diversity into three groups: aerobic-transition, middle anoxic and bottom anoxic zones 43 , similar to what we observed with foraminifera. In our case, the first group including only one sample (3.1 m, SYBH1) which had the highest concentration of TSS was dominated by the monothalamiids.…”
Section: Discussionsupporting
confidence: 86%
“…4, 6). A recent survey focused on the distribution of the bacterial genus Vibrio in the SYBH also showed a clear vertical stratification of the diversity into three groups: aerobic-transition, middle anoxic and bottom anoxic zones 43 , similar to what we observed with foraminifera. In our case, the first group including only one sample (3.1 m, SYBH1) which had the highest concentration of TSS was dominated by the monothalamiids.…”
Section: Discussionsupporting
confidence: 86%
“…isolates previously reported (Tall et al, 2013;Siboni et al, 2016;Wong et al, 2019). However, compared with Vibrio diversity in other temperate and subtropical coastal environments in South China Sea (Li et al, 2019;Möller et al, 2020), our results showed a differently structured Vibrio community. The diversity of Vibrio was higher in winter than in summer, which is consistent with the previous study in the water column of northern Chinese marginal seas (Liang et al, 2019).…”
Section: Discussioncontrasting
confidence: 52%
“…in the present study were Vibrio fortis, Vibrio alginolyticus, and Vibrio hyugaensis, which suggested that the predominance of a specific Vibrio sp. seems to be site-specific as others have reported different predominant Vibrio species in their studies, such as V. alginolyticus, Vibrio campbellii, Vibrio carchariae, Vibrio harveyi, Vibrio owensii, Vibrio parahaemolyticus, Vibrio rotiferianus, and Vibrio splendidus (Maeda et al, 2003;Eiler et al, 2006;Ortiz-Carrillo et al, 2015;Li et al, 2019;Wong et al, 2019). The four major clinically important pathogenic Vibrio species, Vibrio cholerae, V. parahaemolyticus, V. alginolyticus, and Vibrio vulnificus, have been implicated in human diseases such as gastroenteritis and septicemia and even death in immunocompromised patients (Novoslavskij et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Vibrio species are natural residents of aquatic environments [ 13 , 14 ], characterized by high salinity and temperatures varying from 10 to 30 °C [ 15 , 16 , 17 ]. Numerous species (V. cholerae , V. harveyi, V. parahaemolyticus, V. alginolyticus, V. anguillarum, V. splendidus , V. mimicus, V. vulnificus, V. hollisae, and V. fluvialis, etc.)…”
Section: Introductionmentioning
confidence: 99%